1993
DOI: 10.1111/j.1365-2273.1993.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the type of middle ear aspirate have any prognostic significance in otitis media with effusion in children?

Abstract: Two hundred and twenty-two children with chronic, bilateral middle ear effusions were assessed during a 2 year follow-up period. At initial myringotomy the middle ear aspirate was found to be serous in 44 children and mucoid in 178 children. Evaluation at 1 and 2 years post-operatively showed no difference in otoscopic fluid clearance or mean hearing threshold at either follow-up time in relation to either type of fluid. There was no greater need for ventilation tube reinsertion in either group during the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…In a correlation study between the shape of type B tympanogram and the type of secretion there was a highly statistically significant positive correlation ( Table 2) which means that the more flatness of type B tympanogram the more the viscosity of the secretions. This is in agreement with Maw et al [16] who reported that when an effusion is present with a peaked tympanogram, it is more likely that the effusion will be serous, whereas with a flat tympanogram the majority of effusions are mucoid. It has been reported that the three parameters of tympanograms, pressure, compliance and gradient correlated with effusion within the middle ear [9].…”
Section: Discussionsupporting
confidence: 82%
“…In a correlation study between the shape of type B tympanogram and the type of secretion there was a highly statistically significant positive correlation ( Table 2) which means that the more flatness of type B tympanogram the more the viscosity of the secretions. This is in agreement with Maw et al [16] who reported that when an effusion is present with a peaked tympanogram, it is more likely that the effusion will be serous, whereas with a flat tympanogram the majority of effusions are mucoid. It has been reported that the three parameters of tympanograms, pressure, compliance and gradient correlated with effusion within the middle ear [9].…”
Section: Discussionsupporting
confidence: 82%
“…A previous study suggested that different effusions with various levels of enzymes and proteins were correlated with recurrent cases of OME (14). In contrast, Gibb and Mackenzie (7) and Maw et al (15) reported that there was no significant difference of the VT extrusion rate when the middle ear fluid was divided into liquid, glue and very thick glue.…”
Section: Discussionmentioning
confidence: 94%
“…However, the results of previous studies on the relationship between middle-ear effusion characteristics and repetitive insertion of ventilation tubes showed conflicting results. Some reported that the characteristics of middle-ear effusion were not related to recurrence, 12,13 while others reported that mucoid discharge was associated with recurrence. 14 Therefore, the relationship between the nature of middle-ear effusion and recurrence needs to be confirmed in a larger, well-planned study.…”
Section: Discussionmentioning
confidence: 99%